Pengaruh Kualitas Produk Terhadap Loyalitas Pelanggan Dimediasi Kualitas Layanan Di PT Sinergi Gula Pabrik Gula Cinta Manis - ., Ikbal; Helmi, Sulaiman (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of product quality on customer loyalty mediated by service quality at PT Sinergi Gula Nusantara Pabrik Gula Cinta Manis, a producer of Nusa Kita branded sugar. Based on observations, there were customer complaints regarding product quality, such as coarse and moist sugar texture compared to competing brands, as well as complaints about service quality, particularly the company’s slow response when problems occurred.This research employed a quantitative approach with data analysis techniques using Structural Equation Modeling Partial Least Square (SEM-PLS). The research sample consisted of 30 respondents who were customers of the company. The results showed that product quality had a significant effect on customer loyalty with a significance value of 0.000 (≤ 0.05). In addition, product quality also had a significant effect on service quality. However, service quality had no significant effect on customer loyalty (P-Value = 0.259 > 0.05) and was unable to mediate the effect of product quality on customer loyalty (P-Value = 0.262 > 0.05). Therefore, it can be concluded that product quality is the main factor influencing customer loyalty, both directly and not through service quality.